Aufschub . Respite - Farocki, Harun (Farocki, Harun, 2007)
Verzio FF Westerbork camp was established by the Dutch government in October 1939 to intern Jewish refugees from Germany, Austria, Czechoslovakia and Poland. From 1942 to 1944 it served as a transit camp for Jews and Roma before they were deported to extermination camps. In these years, a freight train left every week for Auschwitz-Birkenau, Sobibor, Bergen-Belsen or the Theresienstadt concentration camp. Westerbork was a very strange place. There was a school, a hair-dresser, an orchestra and even a restaurant. These "comforts" were designed by the SS in order to avoid problems during further deportations. Harun Farocki resurrects footage shot by temporary inmate Rudolf Breslauer, who was commissioned by the camp's SS commandant to produce a glossy film about camp life. Breslauer devoted much of his footage to the varied work and activities of the inmates, and also filmed the unloading and loading of incoming and outgoing trains. A close study of the surviving 16mm footage discloses chilling details of everyday life at Westerbork, but also questions generally accepted visual understandings and impressions of the concentration camp system.